Estudio de factibilidad para la implementación de un zoocriadero de guanta (Cuniculus paca); para la producción y comercialización, en la parroquia Santa Cecilia, cantón Lago Agrio, provincia de Sucumbíos - Castillo Torres, John Mauricio (2017)
The present research related to "Feasibility study for the implementation of a guanta (Cuniculus paca) zoocriadero; For the production and marketing, in the parish of Santa Cecilia, canton Lago Agrio, province of Sucumbíos ", has the following objectives: Carry out an analysis of the supply and demand of guanta in the parish of Santa Cecilia; Establish a technical management for the implementation of a zoo for the production and marketing of guanta; Evaluate the financial statements through the TIR, VAN, B / C; And socialize the proposed project with the producers of the Santa Cecilia parish. In the methodology the scientific, analytical, inductive and deductive methods were used. The techniques used were the survey and bibliographic collection and direct observation. The calculated sample was 87 families, which were surveyed. The analyzed elements are: Market study that focuses on primary data on demand and supply in the study sector; Technical study that describes the management techniques of the zoocriadero; Organizational study that highlights the administration and organization for its operation; Financial study that points out the NPV, IRR, RBC; Sensitivity analysis; And, environmental impact study that highlights the influence factors of the zoocriadero for and against the Environment. In this context, the results show that there is a demand of 55175 Lb. Of guanta meat for the year 2016 with an increase of 123830 Lb. For the year 2021, there is no supply of guanta meat in Santa Cecilia, but has been confiscated 204.5 Lb. Of guanta meat in this sector. In the technical study, the project capacity of 5% of the unsatisfied demand was determined, for which a total of 2759 Lb. For the year 2016, 229.9 per month and 7.7 Lb. up to date; The installed capacity consists of 111 females and 22 breeding males distributed in 459m2 of land. The organizational study detailed the amount of labor required for the operation of the zoocriadero, considering that an administrator was in charge of the planning, organization, direction and control of the activities; Secretary-accountant who will keep the accounts; Veterinary adviser for health management of guanta; One worker in charge of upbringing; Two worker who will be responsible for the slaughter of the species and the worker 3 who will be in charge of the direct marketing of guanta. The financial study was determined for eight years of useful life, evaluating two alternatives evaluated: the first alternative with the marketing of guanta in foot and dressing that requires a total investment of $ 140430.67, contributing $ 56172.27 representing 40%, the owner And $ 84,258.40 equivalent to 60% by financial loan; This alternative generates income of $ 46596.57 for the first year; Break-even point of $ 23,971.57, a net profit of $ 7921.42, a net flow of $ 8762.82 at a discount rate of 11.23%; A NPV of 39175.63; IRR of 15.64% and RBC of 1.57; Which reflects its profitability. Meanwhile, the second alternative with the marketing of guanta prepared with an investment of $ 165,892.16, of which 60% corresponding to a total of $ 99535.30 will be financed by bank credit and the remaining 40% of $ 66356.86 by the owner; Evidencing income of $ 7,2592.35 for the first year; Break-even point of 53204.54, a net profit of $ 10,888.85; A net flow of $ 9512.72 with a discount rate of 11.23%; A NPV of $ 71465.28; IRR of 17.15% and RBC of 1.62; So it brings greater profits. It is concluded that the implementation of guanta zoocriadero; For production and marketing, in the parish of Santa Cecilia, canton Lago Agrio, province of Sucumbíos, is feasible to be carried out for being profitable, being therefore recommended to invest in the same.